2022
DOI: 10.1080/17290376.2022.2060295
|View full text |Cite
|
Sign up to set email alerts
|

‘I can't go to her when I have a problem’: sexuality communication between South African adolescent girls and young women and their mothers

Abstract: Parent–adolescent sexuality communication, the process in which parents and their adolescent children discuss sexuality and sexual and reproductive health, is a key component for adolescents’ protective behaviours. Open communication with parents, particularly mothers, enables informed sexual and reproductive health (SRH) decision-making amongst adolescent girls and young women (AGYW). As part of a qualitative study evaluating a South African combination HIV prevention intervention for AGYW, we explored perspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
5
8
0
Order By: Relevance
“…Sex and contraception education is considered taboo in most African cultures [ 14 , 17 , 25 28 ] which is consistent with the reluctance shown by parents or guardians in our study to advise their adolescent children to use contraceptives. In addition, the respondents noted a lack of confidence, inadequacy, and low self-efficacy to provide education regarding contraception, which leaves adolescents vulnerable to unreliable influence from the media and their peers [ 13 , 14 ].…”
Section: Discussionsupporting
confidence: 88%
“…Sex and contraception education is considered taboo in most African cultures [ 14 , 17 , 25 28 ] which is consistent with the reluctance shown by parents or guardians in our study to advise their adolescent children to use contraceptives. In addition, the respondents noted a lack of confidence, inadequacy, and low self-efficacy to provide education regarding contraception, which leaves adolescents vulnerable to unreliable influence from the media and their peers [ 13 , 14 ].…”
Section: Discussionsupporting
confidence: 88%
“…This nding concurs with a study done in South Africa that also found that rumors impede access and utilization of contraceptives (Duby et al, 2022). This is probably due to the societal setup that women discuss issues about their reproduction no matter the information shared.…”
Section: Cognitive Processingsupporting
confidence: 90%
“…Similar to other studies on the continent, youth also accused parents of failing to offer appropriate guidance, not only abandoning informational support to other sources like school teachers, but also offering inadequate material support to the young woman, leading her to seek support elsewhere [ 52 ]. A Botswana study also found parents’ misperceptions about their adolescent children’s relationships to be associated with higher risk activities on the part of the adolescents [ 53 ].…”
Section: Discussionmentioning
confidence: 89%